Distorsi Terminal Komplek QRS pada Infark Miokard Akut Inferior sebagai prediktor kejadian High-degree AV Block - A Sewianto; M Kasim; M Yusak (Jurnal Kardiologi Indonesia, 2007)
Background. ST elevation in acute myocardial infarction can predict the size of infarction, response to reperfusion therapy, and prognosis. Birnbaum et al. showed that early QRS distortion is a reliable prediction of the devel-opment of advanced AV block among patients receiving thrombolytic therapy for inferior wall acute myocardial infarction. Distortion of the ter-minal portion of the QRS in inferior wall acute myocardial infarction based on J point / R wave ratio of more than 50% in at least two leads of the inferior leads (II, III, and aVF). Although transient, development of heart block during inferior infarction is associated with a high in-hospital mortal-ity rate, even they received thrombolytic therapy. Some studies showed ethnic differences in electrocardiogram amplitudes. The aims of this study is to evaluate the correlation between early QRS terminal distortion and high degree AV block among our patients with inferior acute myocardial infarction treated by thrombolytic.Methods and results. This study is a cross-sectional study on patients with inferior wall acute myocardial infarction treated by thrombolytic at National Cardiovascular Center – Harapan Kita, Jakarta during January 2000 until December 2004, that fulfill inclusion and exclusion criteria. They were divided into two groups, those with QRS distortion and without QRS dis-tortion. Correlation between the two groups were analyzed by t test, chi-square and multivariate regression analysis. There are 186 patients, ages between 37 until 72 years old, mostly men (89%) which are 93 patients with QRS distortion and 93 patients without QRS distortion. Those two groups were comparable. With univariate analysis, the group with QRS distortion have higher ST segment deviation (9,61±3,67 vs 7,76±3,53, p=0,001) and higher risk of failed thrombolytic (74,2%vs60,2%, p=0,042).With multivariate regression analysis, there is a significant correlation be-tween QRS distortion and high-degree AV block (OR 2,5; 95% CI 1,04-6,01; p=0,04), most AV block happened during hospitalization.Conclusions. Patients with distortion of the QRS terminal portion in in-ferior acute myocardial infarction and treated by thrombolytic have a higher risk of high-degree AV block during hospitalization, compared to patients without QRS distortion.